Mechanisms and functions of ribosome-associated protein quality control - Joazeiro, Claudio A. P. (Nature reviews, 2019)
Abstract: The stalling of ribosomes during protein synthesis results in the production of truncated polypeptides that can have deleterious effects on cells and therefore must be eliminated. In eukaryotes, this function is carried out by a dedicated surveillance mechanism known as ribosome-associated protein quality control (RQC). The E3 ubiquitin ligase Ltn1 (listerin in mammals) plays a key part in RQC by targeting the aberrant nascent polypeptides for proteasomal degradation. Consistent with having an important protein quality control function, mutations in listerin cause neurodegeneration in mice. Ltn1/listerin is part of the multisubunit RQC complex, and recent findings have revealed that the Rqc2 subunit of this complex catalyses the formation of carboxy-terminal alanine and threonine tails (CAT tails), which are extensions of nascent chains known to either facilitate substrate ubiquitylation and targeting for degradation or induce protein aggregation. RQC, originally described for quality control on ribosomes translating cytosolic proteins, is now known to also have a role on the surfaces of the endoplasmic reticulum and mitochondria. This Review describes our current knowledge on RQC mechanisms, highlighting key features of Ltn1/listerin action that provide a paradigm for understanding how E3 ligases operate in protein quality control in general, and discusses how defects in this pathway may compromise cellular function and lead to disease.
Gesehen am 23.10.2019